The diagnostic utility of TP53 and CDKN2A to distinguish ovarian high-grade serous carcinoma from low-grade serous ovarian tumors - Altman, Alon; Nelson, Gregg S.; Ghatage, Prafull; McIntyre, John B.; Capper, David; Chu, Pamela; Nation, Jill G.; Karnezis, Anthony N.; Han, Guangming; Kalloger, Steve E.; Köbel, Martin (Modern pathology, 2013)
Low-grade serous carcinomas and serous borderline tumors, combined herein and referred to as low-grade serous tumors, show distinct molecular alterations and clinical behaviors compared with high-grade serous carcinomas. The discrimination between low-grade serous tumors and high-grade serous carcinomas can be challenging on small tissue samples, such as cell blocks of paracentesis fluid or biopsies from omental disease. The purpose of this study was to test the ability of TP53 and CDKN2A immunohistochemistry to distinguish between high-grade serous carcinomas and low-grade serous tumors on small tissue samples. Tissue microarrays containing 582 high-grade serous carcinomas, 45 low-grade serous carcinomas, and 49 serous borderline tumors, confirmed by contemporary histopathological review, were stained for TP53 and CDKN2A (DO7 and E6H4 antibody clones, respectively). TP53 was scored as completely absent, wild-type pattern or overexpressed (>60%), and CDKN2A was scored as either negative/patchy (<90%) or block expression (>90%). The combination of the two markers, ie, the TP53 wild-type pattern and CDKN2A patchy expression, had sensitivity for low-grade serous tumors of 89%, a specificity of 93%, a positive predictive value of 68%, and a negative predictive value of 98%. These markers can, therefore, be used on small biopsies/cell blocks to refute a diagnosis of low-grade serous tumors. These findings may inform emerging neoadjuvant therapeutic strategies in advanced ovarian cancers and may be crucial for future clinical trials on molecular-based therapies.